Development of Game-Based Approach Courseware in Learning Computer System Servicing - Shella Mae W. Pareja (Inclusive Society and Sustainability Studies, 2021)
The study focused on the rationale use of technology that is widely spreading around the world. Educational technology is significant in the learning and teaching process. The significance of the developed game-based courseware was to provide instruction and self-drill-and-practice to understand the computer system servicing terms and concepts. This interactive courseware is an additional innovation that will significantly help in the learning and teaching process. The conceptual framework of the study used to organize and varied literature which establishes the scope of education and principles of game-based courseware. The researcher utilized a questionnaire as the primary research instrument. The weighted mean and the standard deviation are used to determine the acceptability of the courseware. To adopt the opportunities offered by developed game-based courseware, it is essential to focus on lessons learned in Computer System Servicing. Features such as peer to peer learning and camaraderie between learners and educators have been found significant in traditional lessons and converted to educational games, as modern technologies move into the informative mainstream. Additional research into the effects and development of game-based approach courseware to classify the role of teachers as facilitators in the game-based approach of learning can establish ways to develop and create educational practices that better engage and motivate students.